Histories of Fetal Knowledge Production in Sweden : Medicine, Politics, and Public Controversy, 1530-2020 - Jülich, Solveig, (Clio Medica ;, 2025)
In this timely and richly illustrated book, a group of multidisciplinary scholars explores the uses and handlings of fetuses, still-born, reproductive organs, and pregnant bodies for knowledge production, including the development of vaccines and pharmaceuticals, in Sweden over five hundred years. By examining the conflicted values and balancing acts of a variety of actors, such as medical experts, legal officials, policymakers, media professionals, disability organizations, and women's movements, it demonstrates how the uses of aborted fetuses for research generated public controversy and became regulated by ethics and law in Sweden. Contributors are: Eva Åhrén, Annika Berg, Elisabet Björklund, Maria Björkman, Maja Bondestam, Isa Dussauge, Helena Franzén, Solveig Jülich, Francis Lee, Tove Paulsson Holmberg, Morag Ramsey, Anton Runesson, Helena Tinnerholm Ljungberg, and Anna Tunlid. See Less